Correlation of tissue concentrations of the pyrethroid bifenthrin with neurotoxicity in the rat - Scollon, Edward J. (2011)
The potential for human exposure to pyrethroid pesticides has prompted pharmacodynamic and pharmacokinetic research to better characterize risk. This work tested the hypothesis that blood and brain concentrations of the pyrethroid bifenthrin are predictive of neurotoxic effects. Adult male Long Evans rats received a single oral dose of bifenthrin dissolved in corn oil. Using figure-eight mazes, motor activity was measured for 1h at 4- and 7-h following exposure to bifenthrin (0-16mg/kg or 0-9mg/kg, respectively; n=4-8/group). Whole blood and brains were collected immediately following motor activity assays. Bifenthrin concentrations in blood and brain were quantified using HPLC/MS/MS. Bifenthrin exposure decreased motor activity from 20% to 70% in a dose-dependent manner at both time points. The relationship between motor activity data and administered dose, and blood and brain bifenthrin concentrations were described using a sigmoidal E max model. The relationships between motor activity and administered dose or blood concentrations were different between the 4- and 7-h time points. The relationship between motor activity and brain concentration was not significantly different between the two time points. These data suggest that momentary brain concentration of bifenthrin may be a more precise dose metric for predicting behavioral effects because the relationship between brain concentration and locomotor activity is independent of the time of exposure.